2016
DOI: 10.1016/j.tiv.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

To involvement the conformation of the adenine nucleotide translocase in opening the Tl+-induced permeability transition pore in Ca2+-loaded rat liver mitochondria

Abstract: The conformation of adenine nucleotide translocase (ANT) has a profound impact in opening the mitochondrial permeability transition pore (MPTP) in the inner membrane. Fixing the ANT in 'c' conformation by phenylarsine oxide (PAO), tert-butylhydroperoxide (tBHP), and carboxyatractyloside as well as the interaction of 4,4'-diisothiocyanostilbene-2,2'-disulfonate (DIDS) with mitochondrial thiols markedly attenuated the ability of ADP to inhibit the MPTP opening. We earlier found (Korotkov and Saris, 2011) that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 83 publications
7
17
0
Order By: Relevance
“…On the other hand, the even greater decline in state 3U DNP and the RCR DNP in the presen ce of NEM (Fig. 5, c and d) is most likely associa ted with the inhibition of succinate dehydrogenase that we observed earlier in similar experiments with RLM [21]. Above results of these experiments with Ca 2+ loaded RHM (Figs.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…On the other hand, the even greater decline in state 3U DNP and the RCR DNP in the presen ce of NEM (Fig. 5, c and d) is most likely associa ted with the inhibition of succinate dehydrogenase that we observed earlier in similar experiments with RLM [21]. Above results of these experiments with Ca 2+ loaded RHM (Figs.…”
Section: Resultssupporting
confidence: 62%
“…In our experiments with Ca 2+ loaded RLM, the Tl + induced MPTP opening in medium containing TlNO 3 and nitrates (KNO 3 , NaNO 3 , NH 4 NO 3 ) was facilitated by inor ganic phosphate [43] but impeded in the presence of both the MPTP inhibitors (ADP, CsA, Mg 2+ ) and the PiC inhibitor mersalyl [15,45]. This allowed us to reach a conclusion regarding the participation of the ANT and the PiC in the Tl + induced MPTP opening in the inner membrane [21,45]. We earlier found that a closure of mitochondrial potassium chan nels (mitoK ATP and mitoK Ca ) increased the MPTP opening [46].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…It was concluded that tBHP oxidizes the vicinal SH-groups of mitochondrial membrane to disulphides, which results in higher gating potential (or higher pore opening probability) (Petronilli et al1994). Stabilization of the ANT in "c" conformation by oxidative stress inductors (tBHP and diamide) due to reaction with thiol groups was found to increase MPT pore opening in the inner mitochondrial membrane (Castilho et al 1996;Halestrap and Brenner, 2003;Halestrap 2010;Korotkov et al 2016). Recently, it has been shown that Ca 2+ -induced swelling enhanced by tBHP was inhibited by ADP and hydrophobic thiol reagent, N-ethylmaleimide, and CsA additionally increased these effects of ADP and N-ethylmaleimide (Korotkov et al, 2016).…”
Section: Figmentioning
confidence: 99%
“…Stabilization of the ANT in "c" conformation by oxidative stress inductors (tBHP and diamide) due to reaction with thiol groups was found to increase MPT pore opening in the inner mitochondrial membrane (Castilho et al 1996;Halestrap and Brenner, 2003;Halestrap 2010;Korotkov et al 2016). Recently, it has been shown that Ca 2+ -induced swelling enhanced by tBHP was inhibited by ADP and hydrophobic thiol reagent, N-ethylmaleimide, and CsA additionally increased these effects of ADP and N-ethylmaleimide (Korotkov et al, 2016). Ca 2+ release from the damaged mitochondria plays a role in this process because EDTA (0.5 mM) inhibited membrane depolarization induced by tBHP.…”
Section: Figmentioning
confidence: 99%